Surface characterization of a new ceramic dental implant - Miranda, Mónica (2015)
This research compares the polished and rough surface of three commercially available dental implants, made of zirconia, titanium grade IV and titanium zirconium. The analysis was done on a Confocal Profilometer at 50x. Results from this analysis show a similar average roughness over the polished surface (Sa value) of the titanium (0,1290 mu m), titanium zirconium (0,1642 mu m) and zirconia implant (0,1523 mu m). However, the results of the analysis of the rough surface show a lower average roughness of the zirconia implant (1,5835 mu m) compared to titanium (3,5986 mu m) and titanium zirconium implant (3,0878 mu m).